Features of contacting of transparent and high-strength measuring tips of active control devices of sizes with products during process of their grinding - E. V. Leun; V. I. Leun (Омский научный вестник)
The article is devoted to the analysis of the load capacity of measuring tips of active control devices (ACD) with the size of the products in their mechanical contact. The value of the depth of indentation of the measuring tips into the product is calculated, which leads to the formation of measurement error. Transparent and high-strength materials for the manufacture of measuring tips are considered. The mode of mechanical interaction for experimental studies of the features of contact between the sapphire tip and the highspeed steel cutter is determined and the value of the specific energy in this contact is calculated. It is shown that the resulting loads, having a ≈40 fold safety margin and corresponding to the quasi-plasticity regime, do not lead to brittle fracture.